Epidermal mosaicism and Blaschko's lines. Issue 9 (September 1993) - Moss, C; Larkins, S; Stacey, M; Blight, A; Farndon, P A; Davison, E V
Abstract : To test the hypothesis that epidermal rather than dermal mosaicism determines Blaschko's lines in hypomelanosis of Ito (HI), we studied the distribution of chromosomal mosaicism in four patients. In two, mosaicism had not been detected in lymphocytes or dermal fibroblasts, but was clearly shown in epidermal keratinocytes; furthermore, the abnormal cell line was confirmed to the hypopigmented epidermis and the normal epidermis contained only normal cells. Negative findings in the other two patients might be because of mosaicism which was undetected either because it was submicroscopic or because it was present in melanocytes, which have not yet been studied. These preliminary results support the ideas that (1) Blaschko's lines represent single clones of epidermal cells; (2) in patients with HI and severe neurological involvement mosaicism, if detectable, is best shown in keratinocytes; and (3) the cytogenetic defect in epidermal cells may be directly responsible for the failure of pigmentation in HI.